A Missiological perspective on a South African Chinese House Church in the light of Alan Hirsch's six elements of "Apostolic Genius" - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2014)
Dissertation (MA Theol)--University of Pretoria, 2013.